Sustainable Beauty Consumption: The Effects of Eco-Labels, Green Advertising, and Social Media Content - Lily Purwianti; Crystal Cornelyanti; Edi Yulianto Putra (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2026)
The rapid expansion of the cosmetics industry has heightened consumer concern for environmental issues, giving rise to green purchase behavior as a response to sustainability challenges. However, green communication instruments such as eco-label, green advertising, and social media content have not fully overcome the attitude-behavior gap, the main obstacle to translating positive attitudes into actual purchases. This study examines the influence of these instruments on green purchase behavior toward environmentally friendly cosmetics, with environmental awareness and attitude as mediating variables, grounded in the Theory of Planned Behavior and Stimulus-Organism-Response framework. A quantitative approach was applied through a questionnaire distributed to 332 respondents in Batam City via judgmental sampling, analyzed using Partial Least Squares Structural Equation Modeling with SmartPLS 4. Testing of fifteen hypotheses showed twelve were supported. All instruments significantly influenced awareness and purchase behavior, whereas only social media content and eco-label shaped attitude, with eco-label showing the strongest influence.